PENGEMBANGAN RUANG PUBLIK TERPADU RAMAH ANAK DI DISTRIK JAYAPURA UTARA, KOTA JAYAPURA (STUDI KASUS: TAMAN IMBI) - Tampun, Gladies J. (Department of Architecture, Engineering Faculty - Sam Ratulangi University, 2021)
Development of Child- Friendly Integrated Public Space in North Jayapura District, Jayapura City is one of the strategic programs in the Jayapura City Medium- Term Development Plan (RPJMD) 2018-2022. The determination of Taman Imbi by the Jayapura City Government is on of the steps in creating child-friendly public spaces in Jayapura. However, the development in Taman Imbi needs to be improve because there are still many criteria for Intergrated Public Space that are Child Friendly which do not match the criteria set out in this research. Qualitative and qualitative descriptive research methods with likert scale analysis were used in the research was conducted to determine the criteria for child-friendly public space indicators. Indicators of criteria for child-friendly public space in Taman Imbi showed availability of Taman Imbi fascilities still need to be improved, namely palyground and sports facilities.